2011
DOI: 10.1056/nejmoa1010821
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of an Impedance Threshold Device in Out-of-Hospital Cardiac Arrest

Abstract: BACKGROUND The impedance threshold device (ITD) is designed to enhance venous return and cardiac output during cardiopulmonary resuscitation (CPR) by increasing the degree of negative intrathoracic pressure. Previous studies have suggested that the use of an ITD during CPR may improve survival rates after cardiac arrest. METHODS We compared the use of an active ITD with that of a sham ITD in patients with out-of-hospital cardiac arrest who underwent standard CPR at 10 sites in the United States and Canada. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 191 publications
(136 citation statements)
references
References 23 publications
(29 reference statements)
0
132
0
4
Order By: Relevance
“…The baseline survival rate was estimated from patients with a first recorded rhythm of ventricular fibrillation or pulseless ventricular tachycardia who received at least two shocks in previous ROC trials. 22,23 The projected difference in survival with amiodarone was estimated from a previous trial database 7 and was the comparison for which this trial was powered.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline survival rate was estimated from patients with a first recorded rhythm of ventricular fibrillation or pulseless ventricular tachycardia who received at least two shocks in previous ROC trials. 22,23 The projected difference in survival with amiodarone was estimated from a previous trial database 7 and was the comparison for which this trial was powered.…”
Section: Discussionmentioning
confidence: 99%
“…Survival status and neurologic function at hospital discharge and beyond has become a standard endpoint for cardiac resuscitation trials, but access to this data is limited by patients/ families who decline consent and those patients who are lost to follow-up. 6,7 The rate of missing outcome data due to declined consent in cardiac arrest trials performed under EFIC is poorly reported. The LINC Trial (mechanical CPR vs. standard CPR) reported a 0.3% (seven of 2,593) consent withdrawal rate, and 0.6% of patients had missing outcome data for their survival to hospital discharge analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 The combination of ITD with active compression-decompression CPR may be a reasonable alternative to conventional CPR in settings with available equipment and properly trained personnel. 16,17 Conventional manual chest compressions remain the standard of care for the treatment of cardiac arrest, but mechanical chest compression devices may be a reasonable alternative for use by properly trained personnel.…”
Section: Advanced Life Support-adultmentioning
confidence: 99%